Pointwise stabilization of the Poisson integral for the diffusion type equations with inertia - Malytska, H.P.; Burtnyak, I.V. (Carpathian Mathematical Publications, 2016)
In this paper we consider the pointwise stabilization of the Poisson integral for the diffusion type equations with inertia in the case of finite number of parabolic degeneracy groups. We establish necessary and sufficient conditions of this stabilization for a class of bounded measurable initial functions.